2014
DOI: 10.1371/journal.pone.0113980
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CTGF Single-Chain Variable Fragment Dimers Inhibit Human Airway Smooth Muscle (ASM) Cell Proliferation by Down-Regulating p-Akt and p-mTOR Levels

Abstract: Connective tissue growth factor (CTGF) contributes to airway smooth muscle (ASM) cell hyperplasia in asthma. Humanized single-chain variable fragment antibody (scFv) was well characterized as a CTGF antagonist in the differentiation of fibroblast into myofibroblast and pulmonary fibrosis in our previous studies. To further improve the bioactivity of scFv, we constructed a plasmid to express scFv-linker-matrilin-6×His fusion proteins that could self-assemble into the scFv dimers by disulfide bonds in matrilin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Further, reducing the levels of p-Akt and p-mTOR suppressed smooth muscle fibrosis in asthma 28 , and rapamycin suppressed asthma onset by inhibiting mTOR signaling 26 . However, despite studies supporting the involvement of mTOR in asthma, controversy exists over the effects of rapamycin treatment in asthma, especially its ability to suppress airway inflammation and airway hyperreactivity 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, reducing the levels of p-Akt and p-mTOR suppressed smooth muscle fibrosis in asthma 28 , and rapamycin suppressed asthma onset by inhibiting mTOR signaling 26 . However, despite studies supporting the involvement of mTOR in asthma, controversy exists over the effects of rapamycin treatment in asthma, especially its ability to suppress airway inflammation and airway hyperreactivity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the role of mTOR in asthma: airway inflammation was inhibited by reducing the activation of PKC-δ in the mTOR pathway 26 , and airway remodeling was shown to tightly associated with high levels of mTOR expression in an asthmatic mouse model 27 . Further, reducing the levels of p-Akt and p-mTOR suppressed smooth muscle fibrosis in asthma 28 , and rapamycin suppressed asthma onset by inhibiting mTOR signaling 26 . However, despite studies supporting the involvement of mTOR in asthma, controversy exists over the effects of rapamycin treatment in asthma, especially its ability to suppress airway inflammation and airway hyperreactivity 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that airway inflammation is suppressed by reducing the activation of the mTOR pathway in asthma 35 and that the AKT/mTOR/p70S6K/GSK pathways play an important role in regulating the cell cycle of lung epithelial cells 36 . Therefore, we explored the effects of DK-1014 on the AKT pathway and found that DK-1014 suppressed the phosphorylation of downstream effectors (i.e., mTOR, p70S6K and GSK) and AKT phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggested that the anti-apoptotic function of TAZ may be relevant with the up-regulation of CYR61 and CTGF and the decrease in Akt phosphorylation which leads to cell apoptosis [ 25 , 26 , 52 , 53 ] may be a mechanism for Celastrol-induced cell apoptosis. On the other hand, some studies indicated that CYR61 and CTGF could increase the phosphorylation of Akt [ 54 56 ]. Hence, TAZ may restore Celastrol-induced cell apoptosis by stimulating Akt signalling pathway activation via up-regulation of CYR61 and CTGF.…”
Section: Discussionmentioning
confidence: 99%